Measuring Unfair Inequality: Reconciling Equality of Opportunity and Freedom from Poverty - Paul Hufe; Ravi Kanbur; Andreas Peichl (Center for Economic Studies and ifo Institute (CESifo), 2018)
Rising income inequalities are widely debated in public and academic discourse. In this paper, we contribute to this debate by proposing a new family of measures of unfair inequality. To do so, we acknowledge that inequality is not bad per se, but that its underlying sources need to be taken into account. Thereby, this paper is the first to reconcile two prominent fairness principles, namely equality of opportunity and freedom from poverty, into a joint measure of unfair inequality. Two empirical applications provide important new insights on the development of unfair inequality both over time (in the US) and across countries (in Europe). First, unfair inequality shows different time trends and country rankings compared to total inequality. Second, average unfair inequality doubles when complementing the ideal of an equal opportunity society with poverty aversion. Furthermore, we show that an exclusive focus on top incomes may misguide fairness judgments.
Keywords: D31; D63; I32; 330; inequality; equality of opportunity; poverty; fairness; measurement